Tyrosinase inhibitory activity of flavonoids from artocarpus lowii king - Jamil, Shajarahtunnur (Penerbit UTM Press, 2014)
Tyrosinase inhibitory activity was studied on the crude extracts and flavonoids successfully isolated from the leaves and heartwoods of Artocarpus lowii King. The flavonoids were fully characterized spectroscopically as isobavachalcone (1), 4-hydroxyonchocarpin (2), 2',4'-dihydroxy-4-methoxy-3'- prenyldihydrochalcone (3), 2',4'-dihydroxy-3,4-(2",2"-dimethylchromeno)-3'-prenyldihydrochalcone (4), artocarpin (5), cycloheterophyllin (6) and 4',5-dihydroxy-6,7-(2,2-dimethylpyrano)-2'-methoxy-8-γ,γ- dimethyl allylflavone (7). Tyrosinase inhibitory activity of the samples was determined against mushroom tyrosinase using ELISA microplate reader. Cycloheterophyllin (6) exhibited an excellent inhibitory activity against mushroom tyrosinase comparable to the standard kojic acid with the IC50 value of 52.5 μg/mL (88.3%).